2009
DOI: 10.1111/j.1365-2591.2009.01637.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemostatic effect and tissue reactions of methods and agents used for haemorrhage control in apical surgery

Abstract: Haemostasis in experimental bone defects is most effectively accomplished by using Expasyl + Stasis or electro cauterization. However, the bone defects should be freshened with a rotary instrument before suturing so as not to compromise healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 14 publications
0
28
0
4
Order By: Relevance
“…Previous experimental work on this area of research has been performed both in inferior animals, like Wistar rat (21), Sprague-Dawley rat (16,22,23), New Zealand rabbit (10,(24)(25)(26) or Burgundy rabbit (13,14), or in higher order species, like Beagle dogs (17,27,28), or swines (15,29). Previous experimental work on this area of research has been performed both in inferior animals, like Wistar rat (21), Sprague-Dawley rat (16,22,23), New Zealand rabbit (10,(24)(25)(26) or Burgundy rabbit (13,14), or in higher order species, like Beagle dogs (17,27,28), or swines (15,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experimental work on this area of research has been performed both in inferior animals, like Wistar rat (21), Sprague-Dawley rat (16,22,23), New Zealand rabbit (10,(24)(25)(26) or Burgundy rabbit (13,14), or in higher order species, like Beagle dogs (17,27,28), or swines (15,29). Previous experimental work on this area of research has been performed both in inferior animals, like Wistar rat (21), Sprague-Dawley rat (16,22,23), New Zealand rabbit (10,(24)(25)(26) or Burgundy rabbit (13,14), or in higher order species, like Beagle dogs (17,27,28), or swines (15,29).…”
Section: Discussionmentioning
confidence: 99%
“…Delay in collagen deposition can lead to an increase in the risk of inflammatory reactions at the surgical bed and worsen the final restitution ad integrum. This aggressive management can lead to abnormalities of the sealing material and their properties (14). Kopac et al (30) showed an intense inflammatory reaction in the soft tissue of the animals treated with aluminum chloride.…”
Section: Discussionmentioning
confidence: 99%
“…Expasyl™ alone or in combination with ferric sulfate appeared to be the most efficient agent, and the inflammatory tissue reactions were limited to the bone defects, never extending into the surrounding tissues. In a similar study, Jensen et al (14) found that the foreign body reactions produced in the presence of Expasyl™ and ferric sulfate did not occur if the bone cavity was refreshed with rotary instruments and irrigation.…”
Section: Introductionmentioning
confidence: 89%
“…The authors therefore recommended cleaning the surgical wound with a curette and refreshing the bone walls with a rounded drill before wound closure. Jensen et al (10) noted that adverse reactions to Expasyl™ did not occur if the traces of the paste were eliminated from the bone crypt with rotary instruments. In our study we favored bleeding within the bone cavity before suturing, and the teeth in the Expasyl™ group had a better prognosis than those belonging to the anesthetic solution with vasoconstrictor group after 12 months of follow-up and on occasion of the last control visit (non significant differences) – though not so at the first control after 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Expasyl™ alone or in combination with ferric sulfate was found to be the most effective agent, and the inflammatory reactions were limited to the bone defects, with no spread to the surrounding tissues. Jensen et al (10) used the same study design to compare the effects of 5 hemostatic techniques: Expasyl™ + Stasis®, Expasyl™ + Stasis® + bone crypt freshening with a drill, Spongostan®, Spongostan® + adrenaline, and electrocautery. The most effective methods for reducing bleeding were Expasyl™ + Stasis® and electrocautery, but adverse tissue reactions were observed (necrotic bone, inflammatory cells, absence of bone repair).…”
Section: Introductionmentioning
confidence: 99%